Pendidikan Kristen dalam Kearifan Lokal Falsafah Jawa Upaya Membangun Iman Keluarga - Carolina Etnasari Anjaya (Institut Agama Kristen Negeri Kupang, 2021)
Javanese philosophy as a cultural heritage has rarely been introduced and taught to the present generation. In fact, there are many Javanese philosophies regarding the nature of life that can be used as teaching materials in family Christian education. The fading of this culture makes this research conducted in order to provide a view to Christian families that Javanese philosophy can be a bridge for faith education in the family. The research method is through a qualitative approach. To describe the meaning of the four Javanese philosophies that were adopted as the core of this research discussion and their relationship to Bible truth and how they are applied in family education. The conclusion of the research is that the Javanese philosophy: Sangkan Paraning Dumadi, Urip Kui Urup, Urip Mung Mampir Ngombe, and Nrimo Ing Pandum contains the meaning of teaching in accordance with the truth of God's word. Javanese philosophy can be taught and applied in the family as a Christian education to strengthen the family's faith. But the teaching must be based on the truth of the Bible because the Bible is the source of all knowledge and wisdom.